Pembentukan Regulasi Crowdfunding Based Donation Sebagai Optimalisasi Hukum Financial Technology Dengan Studi Perbandingan Sistem Hukum Denmark - Ferdiansyah, Reza; Nurfajriana, Syifa; Nugroho, Andriyanto Adhi (Media Hukum Indonesia (MHI), 2024)
Globalization and the Fourth Industrial Revolution have driven significant changes across various sectors, including technology, economics, and law. The rapid advancement of technology and internet access in Indonesia has led to a surge in the use of fintech services, particularly crowdfunding. Crowdfunding, rooted in microfinance and crowdsourcing, has become a popular method for raising funds via the Internet. Despite its innovative nature, crowdfunding practices in Indonesia face several challenges, particularly regarding regulation and legal protection. Current crowdfunding regulations in Indonesia still refer to Law No. 9 of 1961 on the Collection of Money or Goods, which does not accommodate electronic systems. This has resulted in the potential misuse of donation funds not being adequately addressed. This study employs normative legal research methods with a statute approach and a conceptual approach. The study examines the regulation of donation-based crowdfunding in Indonesia and compares it with Denmark, which has more detailed regulations through the Danish Fundraising Act. Denmark has implemented stringent oversight mechanisms to ensure transparency and accountability in fundraising activities, which can serve as a valuable reference for Indonesia in drafting similar regulations. Legal protection for donation-based crowdfunding practices is crucial to ensure public trust and the sustainability of these activities